Prevalence of SARS -CoV-2 IgG/IgM antibodies among patients in Zakho City, Kurdistan, Iraq - Ali Yahya Saeed; Mahde Saleh Assafi; Hemin Esmael Othman; Hogir Mohammed Shukri (Journal of Infection in Developing Countries)
Introduction: In 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the agent of Coronavirus Disease 2019 (COVID-19), spread all over the world. This global pandemic spread rapidly to more than 195 countries and caused over 200 million infections with a mortality rate of 2%. This study aimed to detect seropositivity against the SARS-CoV-2 virus among outpatients, symptomatic and asymptomatic individuals.